The Macroeconomic Effects of Structural Reforms in Latin America and the Caribbean - David, Antonio (IMF Working Papers; Working Paper ;, 2020)
This paper estimates the macroeconomic effects of structural reforms in Latin America and the Caribbean (LAC) using the dataset constructed by Alesina and others (2020). We find that large changes in the reform index have positive effects on GDP and employment that reach 2 percent after 5 years. Furthermore, reforms boost investment, exports, imports, and reduce export concentration, in addition to favoring tradable sectors. Nonetheless, the results also indicate that the effects of reforms have not been uniform across different segments of the population. These findings bring to the forefront the need to consider accompanying policies to ensure that reforms promote inclusive growth. Moreover, evidence from country case studies using the synthetic control method point to heterogeneous effects of reforms on income per capita.